(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Aspiration of gastric contents can be a serious perioperative complication, attributing up to 9% of all anesthesia-related death. Point-of-care gastric ultrasound has become a useful tool for the perioperative assessment of gastric content and volume, helping the anesthesiologist to assess the risk of regurgitation and aspiration. Objectives: Determine the rate of stomach fullness by ultrasound and evaluate some factors related to gastric fluid residue in emergency surgery patients. Research objects and methods: We performed a prospective observational study in 30 patients undergoing emergency surgery, over 18 years old, with ASA I-III, willing to participate in the study. Patients with prior gastrointestinal surgery and parturients were excluded from present study. Gastric antrum in both suspine and right lateral decubitus positions were measured using ultrasound. Gastric content (empty, fluid, solid) was noted, and the gastric residual volume was calculated, which was subsequently correlated with various patient factors. A full stomach was defined as any solid content or ≥ 1.5 ml/kg of gastric residual volume. Results: 8/30 patients (26.7%) were determined to have a full stomach; the average gastric residual volume was about 62.63 ml, patients with hyperglycemia or being overweight were associated with increased gastric residual volume and fasting and drinking time were correlated with gastric residual volume but not statistically significant (p > 0.05). Conclusions: The average gastric residual volume was 62.63 ml and 26.7% patients had a full stomach. A risk of increasing gastric residual volume existed in patients with hyperglycemia or overweight. Fasting and drinking time were not reliable in patients undergoing emergency surgery. Bedside ultrasonography could potentially become a clinically useful noninvasive tool to accurately determine gastric content and volume with significant implications for perioperative aspiration risk assessment.